Metodologi Kontekstual dalam Tafsir Ayat Hukum: Studi Literatur atas Tafsir Klasik dan Kontemporer - Kusumawardana, Muhammad Ardi (TSAQOFAH, 2024)
The interpretation of legal verses in the Qur'an undergoes significant methodological dynamics between classical and contemporary mufassirs, which raises issues of relevance and adaptability in the modern social context. This study aims to explore and compare contextual methodologies in the interpretation of legal verses between classical and contemporary periods. The method used is a literature study with a comparative analysis approach to classical interpretations such as Al-Tabari, Al-Qurtubi, and Ibn Kathir and contemporary interpretations such as Quraish Shihab and Abdullah Saeed. The results show that contemporary mufassirs more often use a contextual approach that considers current social and cultural dynamics, while classical mufassirs tend to use a literal textual approach. The findings support the hypothesis that contextual methodology is more relevant and adaptive to social change compared to classical textual methods. This research produces the "Contextual-Textual Tafsir Integration Theory" (CTIT) which offers a synthesis between textual and contextual approaches. The implication of this study is the need for integration between textual and contextual approaches to develop a more holistic and responsive tafsir methodology, which not only maintains the classical intellectual heritage but also meets the needs of modern society.